Evaluación nutricional en gestantes uuarias del Subcentro de Salud Chontacruz de la ciudad de Loja - Salinas González, Gabriela Maritza (2019)
Nutritional status is the situation in which a person is in relation to the intake and physiological adaptations that take place after the entry of nutrients, therefore, the evaluation of nutritional status is the action and effect of estimating, assessing and calculating the condition in which an individual is found according to the nutritional changes that may be affected (Costales, 2017). The objective of this study was to evaluate the nutritional status of the pregnant users of the Subcentro de Salud Chontacruz of Loja, for that 201 pregnant women who attended the prenatal check-ups during the period of October 2018 - April 2019, were included. A cross-sectional descriptive study and a structured survey was used as a tool, also data from the clinical histories was also collected. The most frequent age group was between 21 to 25 years old (35%), with medium economic situation (79%), married, with secondary education (59%) and dedicated to domestic chores (78.6%). ; more than half of the patients presented a normal IMC in the first control (55.2%), maintaining up to the fifth control within the gain curve (76.1%). In addition, the informative cards were given to the users about an adequate diet, the same ones that were socialized with the pregnant women. KEYWORDS: intake, pregnant women, body mass index, nutritional status, overweight, physiological adaptation, conception, nutrition.